Toward Situated Media: Engaging Elementary School Teacher-Candidates in Learning English Vocabularies with Craft Project-Based Learning - Husna Imro'athush Sholihah; Vivi Astuti Nurlaily (Research And Innovation In Language Learning (RILL), 2021)
This research, a part of a larger study, is aimed at investigating the enactment of handy craft project-based learning to the elementary teacher candidates to promote English vocabulary mastery and shared information. Grounded in DBR design, a classroom of elementary teacher candidates in a private teacher educator of private university in Indonesia were recruited in the study. All collected data were from questionnaire and interview. The results show the participants enjoyed and felt fun in designing and employing the designed crafts in classroom instruction during the learning cycles. In spite of the limitation, the project was successful and received positive responses from the participants